2003
DOI: 10.1046/j.1439-0523.2003.00856.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the 7DL.7Ag translocation from Lophopyrum elongatum on wheat yield and related morphophysiological traits under different environments

Abstract: The 7DL.7Ag translocation from Lophopyrum elongatum that carries Lr19, a leaf rust resistance gene, was found to be associated with a significant increase in grain yield under irrigated, disease-free conditions, but a generally lower yield under moisture stress conditions. These studies, however, involved a limited number of genetic recipients and environments, and the effect of the translocation on physiological traits was not considered. We examined the translocation effect in six different recipient genotyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
51
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 25 publications
2
51
1
Order By: Relevance
“…The development of isogenic lines for the distal 7EL segment in durum wheat lines UC1112 and UC1113 and for the proximal 7EL segment in hexaploid line 1-96, may provide valuable information for the location of the 7EL chromosome region associated with yield increases under irrigated conditions (Monneveux et al 2003;Singh et al 1998). …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The development of isogenic lines for the distal 7EL segment in durum wheat lines UC1112 and UC1113 and for the proximal 7EL segment in hexaploid line 1-96, may provide valuable information for the location of the 7EL chromosome region associated with yield increases under irrigated conditions (Monneveux et al 2003;Singh et al 1998). …”
Section: Discussionmentioning
confidence: 99%
“…The original 7E chromosome was incorporated into cultivars 'Agatha' (Knott 1980), 'Oasis', and others (Monneveux et al 2003;Rajaram 2001). Agronomic characterization of several isogenic lines for this translocation demonstrated that the presence of the 7E Communicated by P. Langridge segment was associated with a yield increase under irrigated conditions (Monneveux et al 2003;Singh et al 1998).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One specific translocation on the 7DL chromosome of wheat, called variously 7Ag.7DL, Agatha or T4 [3][4][5], from Thinopyrum ponticum (tall wheatgrass), contained a number of characterized genes including Lr19 for leaf rust resistance, Sr25 for stem rust resistance, Sd1, a segregation distortion gene, and a linked gene deleterious for yellow pigment endosperm colour. This T4 translocation has also been associated with higher grain yield, anthesis biomass and delayed maturity in a number of genetic backgrounds [6][7][8]. Interestingly, the higher yield potential is only expressed under non-moisture stress conditions where yields exceed 2.5 tonnes per hectare [8].…”
Section: Introductionmentioning
confidence: 97%
“…This T4 translocation has also been associated with higher grain yield, anthesis biomass and delayed maturity in a number of genetic backgrounds [6][7][8]. Interestingly, the higher yield potential is only expressed under non-moisture stress conditions where yields exceed 2.5 tonnes per hectare [8].…”
Section: Introductionmentioning
confidence: 97%